Review of Power Electronics Technologies in the Integration of Renewable Energy Systems - Vijaychandra Joddumahanthi; Łukasz Knypiński; Yatindra Gopal; Kacper Kasprzak (Applied Sciences)
Power electronics (PE) technology has become integral across various applications, playing a vital role in sectors worldwide. The integration of renewable energy (RE) into modern power grids requires highly efficient and reliable power conversion systems, especially with the increasing demand for grid controllability and flexibility. Advanced control and information technologies have established power electronics converters as essential enablers of large-scale RE generation. However, their widespread use has introduced challenges to conventional power grids, including reduced system inertia and stability issues. This article studies the critical role of power electronics in the grid integration of RE systems, addressing key technical challenges and requirements. A special focus is given to the integration of wind energy, solar photovoltaic, and energy storage systems. This paper reviews essential aspects of energy generation and conversion, including the control strategies for individual power converters and system-level coordination for large-scale energy systems. This article additionally includes grid codes that pertain to wind and photovoltaic systems, as well as power conversion and control technologies. Finally, it outlines the future research directions, aimed at overcoming emerging challenges and advancing the seamless integration of RE systems into the grid, thereby contributing to the development of more sustainable and resilient energy infrastructure.